Characterization of flow dynamics and reduced-order description of experimental two-phase pipe flow. (August 2018) - Viggiano, Bianca; Skjæraasen, Olaf; Schümann, Heiner; Tutkun, Murat; Cal, Raúl Bayoán
Highlights: Interface characteristics captured by POD. First ten eigenmodes yield cyclical slug behavior. POD coefficients correlated with the liquid holdup of the slug flow. Abstract: Two-phase dispersed and slug flows in a pipe are investigated using proper orthogonal decomposition (POD). The data are acquired through tomographic reconstruction of X-ray measurements, where holdup, cross-sectional phase distributions and phase interface characteristics are obtained. Instantaneous phase fractions of the flow fields are analyzed and reduced-order descriptions of the flow are achieved. The dispersed flow displays coherent features for the first few modes near the center of the pipe, representing the liquid-liquid interface location while the slug flow case shows coherent features that correspond to the cyclical formation of the slug in the first ten modes. For slug flow, the first two modes capture the liquid-dominated slug body region and the Taylor bubble/liquid film region, respectively. The reconstructions of the fields indicate that main features are observed in the low order descriptions utilizing less than one percent of the degrees of freedom of the full order descriptions. POD temporal coefficients a 1, a 2 and a 3 show interdependence for the slug flow case. The coefficients also describe the phase fraction holdup as a function of time for both dispersed and slug flow.